DESEMPENHO DE FRANGOS DE CORTES CRIADOS EM DIFERENTES DENSIDADES DE CRIAÇÕES NA FASE INICIAL (1-21 DIAS) - FERREIRA, Thales Silva; OLIVEIRA, Andréia Fróes Galuci; HENRIQUE, Cleoneide dos Santos; SOUZA, Jéssica Andrade Diniz; ANDRADE, Agner de Freitas; MARTINS, Vinícius Da Silva Freitas (ANAIS DO ENIC, 2017)
-